Ungrammatical Construction: An Analysis of the Causes and Types of the Ungrammatical Construction - Desfianur Ardhi; Sudarsono; Ikhsanudin (Jurnal Syntax Admiration, 2023)
The present research is about analysis on ungrammatical constructions encountered in the texts written by the 3rd semester undergraduate students of English Language Education Program of Tanjungpura University. The objective of the study is to describe the types of the ungrammatical constructions and the causes of the ungrammatical constructions. The method of research is descriptive. The research participants were 34 students of the 3rd semester undergraduate students of English Language Education Program of Tanjungpura University. The data were collected from corpus written by the students. The ungrammaticalities occurred in the students’ text. They were 496 errors encountered by the students. 312 errors related to phrasal errors and 184 related to clausal errors. The phrasal-related errors affected the area of noun phrase (37%), gerund phrase (13%), verb phrase (17%), infinitive phrase (12), prepositional phrase (12%), adjective phrase (7%), and adverb phrase (2%). The clausal-related errors were alternating form (49%), omission (33%), simple addition (15%), double marking (2) and misplaced subject and verb (1%). The sources of these errors were interlingual (2,9%) and intralingual (97,1%).